Assessing and managing coronary microcirculation dysfunction in acute ST-segment elevation myocardial infarction. (1st February 2019) - Armstrong, Richard; De Maria, Giovanni Luigi; Scarsini, Roberto; Banning, Adrian P.
ABSTRACT: Introduction : Microvascular dysfunction in the setting of acute ST-segment elevation myocardial infarction (STEMI) is an indicator of poor long-term prognosis. Prompt assessment and pharmacological or procedural therapy (prophylactic or post onset of dysfunction) may improve outcomes in STEMI post-primary percutaneous intervention. Areas covered : The aim of this review is to provide a comprehensive analysis of the evidence available about the assessment and management of coronary microcirculatory injury/dysfunction in STEMI. We also aim to elucidate the possible strategies that could be applied in clinical practice to support the application of already available or novel therapeutic strategies for the prevention and management of microvascular impairment. Expert commentary : There are multiple established methods in assessing microvascular dysfunction, both non-invasively and invasively. Invasive physiological measurements allow real-time assessment of microvascular dysfunction and have prognostic cut-off values. Multiple therapeutic modalities exist for both preventing and treating microvascular dysfunction. These can be either pharmacological or mechanical, and there is no algorithm to guide if, how and when to apply them. Future research into both procedural and pharmacological therapy guided by physiological measurements is needed, with the aim of recognizing high-risk patients who would benefit from therapy.